2017
DOI: 10.1080/2000656x.2017.1319846
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin receptors in Dupuytren’s disease: a target for pharmacological treatment?

Abstract: These findings have opened a new avenue for future research involving ACE inhibitors, AT2 agonists, and AT2 antagonists in Dupuytren's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Although beyond the scope of this report, it is exciting to speculate on the possibility of targeting the ESC-like population within DD using RAS modulators, such as ACE inhibitors as previously proposed 43 and inhibitors of cathepsins, such as curcumin 44 for cathepsin B, pepstatin for cathepsin D, 45 and chymostatin 45 for cathepsin G, in the treatment of this condition.…”
Section: Discussionmentioning
confidence: 92%
“…Although beyond the scope of this report, it is exciting to speculate on the possibility of targeting the ESC-like population within DD using RAS modulators, such as ACE inhibitors as previously proposed 43 and inhibitors of cathepsins, such as curcumin 44 for cathepsin B, pepstatin for cathepsin D, 45 and chymostatin 45 for cathepsin G, in the treatment of this condition.…”
Section: Discussionmentioning
confidence: 92%
“…The ESC-like population on the endothelium of the microvessels surrounding cords and nodules of DD expresses components of the RAS: PRR, ACE, AT 1 R, AT 2 R, with ACE and PRR also expressed on the pericytes ( 36 ). Stephen et al ( 49 ) report AT 2 R being more abundant than AT 1 R in DD ( 218 ), which is interesting given the largely unknown role of AT 2 R, which is expressed abundantly in fetal tissue compared to adult tissues. This suggests a potential therapeutic role of AT 2 R antagonists and ACEIs for DD ( 219 ).…”
Section: Embryonic Stem Cell-like Cells the Renin-angiotensin System ...mentioning
confidence: 96%
“…More recently, non-operative treatment with Clostridium histolyticum collagenase injection has been used ( 216 ). The long-term outcomes and complications remain unknown, with repeated use being associated with neuromuscular and coagulation disorders ( 217 , 218 ).…”
Section: Embryonic Stem Cell-like Cells the Renin-angiotensin System ...mentioning
confidence: 99%
“…Dupuytren's disease is another fibrotic disease, for which an overactivation of the local RAS has been described. [66] A recent study dergoing open partial fasciectomy were implanted under the dorsal skin of nude mice. [67] The authors found that a 5-day treatment with C21 significantly inhibited myofibroblast proliferation in the transplanted Dupuytren's disease cord specimens.…”
Section: Dupuytren's Diseasementioning
confidence: 99%
“…Dupuytren's disease is another fibrotic disease, for which an overactivation of the local RAS has been described. [ 66 ] A recent study by Chisholm et al tested treatment with the AT 2 R agonist C21 in a xenograft model of Dupuytren's disease in order to investigate the therapeutic potential of the anti‐fibrotic properties of the AT 2 R. For this purpose, Dupuytren's disease cord specimens from patients undergoing open partial fasciectomy were implanted under the dorsal skin of nude mice. [ 67 ] The authors found that a 5‐day treatment with C21 significantly inhibited myofibroblast proliferation in the transplanted Dupuytren's disease cord specimens.…”
Section: The Cutaneous Renin‐angiotensin System Under Pathophysiologimentioning
confidence: 99%